Null effect of scratches made by curling rocks - Shegelski, M. R.; Lozowski, E. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
There is disagreement in the literature as to whether scratches made by curling rocks affect the motion of subsequent curling rocks. The aim of this investigation is to provide unequivocal experimental evidence to resolve this disagreement. Such evidence has been obtained by comparing the curl distances (total lateral deflections) of rocks sliding over ice with no scratches to curl distances of rocks sliding over ice completely covered with scratches made by previous curling rocks. The result of this simple experiment is that there is no appreciable difference in the curl distances between the two ice conditions. The conclusion is that the scratches made by curling rocks do not affect the motion of other curling rocks and that the lateral deflection of curling rocks cannot solely be due to scratches made by curling rocks.